How to teach geography - Quintard, Alice Julia (My University, 1895)
Introduction: Ruskin says that it is necessary for an educated man to know, “Where he is—that is to say, what kind of a world he has got into; how large it is; what kinds of creatures live in it, and how; what it is made of and what can be made of it.” We agree with Ruskin and say that a man cannot be educated without knowing this, and how is he to know this except by the study of geography. We shall admit then that the study of geography is of the utmost importance to the education of man. Someone has said that, “Geography properly pursued, touches upon all the other branches, whether of literature, science, or art, and is the foundation stone upon which rests the whole superstructure of human knowledge. It should form a background, a chessboard, on which to marshal the ever-changing events of life.” Steel says, “To teach is something that most of our teachers need to be taught, and of geography this is perhaps unusually true.” We propose in this production to give a few hints that may be of some use to those who are thinking of becoming teachers.
Citation: Quintard, Alice Julia. How to teach geography. Senior thesis, Kansas State Agricultural College, 1895.
Morse Department of Special Collections
Keywords: Geography; Teaching; Education; Theses; Manuscripts (documents)